Zrinski Family in the Croatian Historiographic Discourse. A Case-Study in the Construction of National Identity - Štefanec, Nataša (Array, 2009)
The Zrinski family today is omnipresent in every syntheses of the national history. Historiography on the Zrinski family as well as the editions of sources are numerous. From the 19th century, the best Croatian historians researched the Zrinski family in various contexts. Two facts remain. The Zrinskis, as one of the most important phenomena in Croatian and Hungarian histories are still surprisingly inadequately researched. Serious, complex research results are scarcely used in public or politics. This paper has presented and analyzed the main research tendencies from the historiography on the Zrinski family until the year 2000 as well as dominant trends in the political usage of the Zrinski’s history. It has also outlined directions for some further research. It has come to the conclusion that the popular image of the Zrinskis as national martyrs and heroes rests much more on simplified emotional interpretations (also present in textbooks) than on the research-based accounts. Zrinskis are still a useful motive for ideologies and mythologies. Most cities and villages in Croatia have a street or a square named after Zrinski and Frankopan - though these were often areas that were in no way connected with the Zrinski family. This was and it is largely due to the ways in which the professional historiography functions - compartmentalized nationally, disciplinary and methodologically. It was and it is also due to the political usage of the history and to the educational adaptations (and/or simplifications) of historical facts and processes required by political ideologies - though the authoress is convinced that a complex and unrestrained story about the historical experience of the Zrinski family would be a much better textbook, both for political elites and for the people.